The impact of oral semaglutide on glycemic control and weight reduction: a database analysis of dosing effects in Japanese individuals with type 2 diabetes - Ishiguro, Mizuki; Nishimura, Rimei (Frontiers in Endocrinology, 2025)
ObjectiveGLP-1 receptor agonists (GLP-1 RAs) reduce cardiovascular events in type 2 diabetes (T2D), and oral formulations improve accessibility. However, their real-world effectiveness and predictors of response remain unclear. This study assessed the proportions of individuals achieving HbA1c < 7.0% and experiencing ≥3.0% weight reduction after 180 days of maintenance-dose therapy (no dose modification for ≥180 days).MethodsWe retrospectively analyzed 169 participants with T2D (3 mg: n=45; 7 mg: n=92; 14 mg: n=32) treated at a single medical care center in Japan. The cohort included participants with HbA1c ≥ 7.0% at baseline. We evaluated semaglutide changes in HbA1c and weight, and predictors of glycemic response after 180 days of maintenance therapy using logistic regression.ResultsBaseline characteristics included median age 63.0 years, body mass index (BMI) 27.2 kg/m², diabetes duration 10.0 years, and HbA1c 7.7%. Oral semaglutide was initiated as the first or second choice in 45.0% of participants. HbA1c < 7.0% was achieved in 60.0%, 53.3%, and 46.9% of the 3 mg, 7 mg, and 14 mg groups, respectively. Weight reduction ≥ 3.0% occurred in approximately half of participants across all groups. Lower baseline HbA1c (B = -1.330, p < 0.001) and earlier semaglutide use (first/second choice; B = 1.070, p = 0.013) were significant predictors of HbA1c < 7.0%.ConclusionApproximately 50% of participants across all dosing groups achieved HbA1c < 7.0% after 180 days of maintenance therapy. Weight reduction (≥ 3.0%) occurred frequently in parallel with HbA1c reduction. Early semaglutide use (first/second choice) and lower baseline HbA1c predicted HbA1c < 7.0% on maintenance therapy.